An Investigation of Neurochemical Changes in Chronic Cannabis Users - Newman, Sharlene D.; Cheng, Hu; Schnakenberg Martin, Ashley; Dydak, Ulrike; Dharmadhikari, Shalmali; Hetrick, William; O’Donnell, Brian (Frontiers in Human Neuroscience, 2019)
With the legalization of recreational cannabis (CB) the characterization of how it may impact brain chemistry is essential. Magnetic resonance spectroscopy (MRS) was used to examine neurometabolite concentrations in the dorsal anterior cingulate (dACC) in chronic CB users (N=26; 10 females) and controls (N=24; 10 females). The concentrations of glutamate (Glu), total creatine (tCr), choline (Cho), total N-acetylaspartate (tNAA), and myo-inositol (mI) were estimated using LCModel. The ANCOVAs failed to show significant differences between controls and CB users. Regression analyses were then performed on the CB group to model each neurometabolite to determine its relationship to monthly CB use, sex, the interaction between CB use and sex, and age of CB initiation. tCr was found to be predicted by both monthly CB use and sex. While the regression model was not significant the relationship between monthly CB use and Glu appears to be modulated by sex with the effect of monthly use (dose) being stronger in males. tNAA failed to show an effect of CB use but did reveal an effect of sex with females showing larger tNAA levels. Although the results presented are preliminary due to the small sample size they do guide future research. The results presented provide direction for further studies as they suggest that dose may significantly influence the observance of CB effects and that those effects may be modulated by sex. Studies with significantly larger sample sizes designed specifically to examine individuals with varying usage as well as sex effects are necessary.